Dyssomnias and Parasomnias - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The prevalence of dyssomnias and parasomnias was determined in a longitudinal study of a sample of 2223 infants born in 1997-98 in the province of Quebec, Canada, and reported from the Sleep Disorders Center, Sacre-Coeur Hospital, University of Montreal.